Strategies to Prevent Elderly Suicide: A Delphi Consensus Study. (June 2022) - Barak, Yoram; Fortune, Sarah; Hobbs, Linda; Cheung, Gary; Johari, Nurrul; Zalsman, Gil
Objectives: In the next decades, many countries will become 'ageing societies'. This combined with the current high rates of suicide in later life suggests that many older adults may die by suicide before clinical trials can be conducted to demonstrate the best approaches to prevent late-life suicide. Methods: A New Zealand (NZ) 'expert panel' has reviewed key considerations for suicide prevention interventions in older adults based on existing evidence, where available, and expert opinion. The key considerations were extracted from the current literature. The Delphi survey method was used to reach consensus for identifying interventions to be recommended as part of a national strategy for older adults' suicide prevention. Results: A set of 20 key recommended considerations are presented. The major addition to existing recommendations is the need for 'A suicide prevention strategy for the elderly…' to enhance the national all-ages suicide prevention strategy. Conclusion: The recommended statements are offered for consideration by stakeholder groups preparing new interventions, large-scale public healthcare planning and governmental policy.